Integrated Management of Multiple Sclerosis Spasticity and Associated Symptoms Using the Spasticity-Plus Syndrome Concept: Results of a Structured Specialists' Discussion Using the Workmat® Methodology - Fernandez, Oscar; Costa-Frossard, Lucienne; Martínez-Ginés, Maria Luisa; Montero, Paloma; Prieto-González, Jose María; Ramió-Torrentà, Lluís (Frontiers in Neurology, 2021)
Background: Multiple sclerosis (MS) treatment has radically improved over the last years; however, MS symptoms management is still challenging. The novel Spasticity-Plus syndrome was conceptualized to frame several spasticity-related symptoms that can be addressed together with broad-spectrum medication, such as certain cannabinoid-based drugs. The aim of this project was to gain insight into the Spanish neurologists’ clinical experience on MS spasticity and associated symptoms, and to assess the acknowledgement and applicability of the Spasticity-Plus syndrome concept in patients with MS. Methods: Ten online meetings were conducted using the Workmat® methodology to allow structured discussions. Fifty-five Spanish neurologists, experts in MS management, completed and discussed a set of predefined exercises comprising MS symptoms assessment and its management in clinical practice, MS symptoms clustering in clinical practice and their perception of the Spasticity-Plus Syndrome concept. This document presents the quantitative and qualitative results of these discussions. Results: The specialists considered that polytherapy is a common concern in MS and that simplifying the management of MS spasticity and associated manifestations could be useful. They generally agreed that MS spasticity should be diagnosed before moderate or severe forms appear. According to the neurologist’s clinical experience, symptoms commonly associated with MS spasticity included spasms/cramps (100% of the specialists), pain (85%), bladder dysfunction (62%), bowel dysfunction (42%), sleep disorders (42%), and sexual dysfunction (40%). The multiple correspondence analysis revealed 2 main symptom clusters: spasticity-spasms/cramps-pain, and ataxia-instability-vertigo. Twelve out of 16 symptoms (75%) were scored >7 in a 0-10 QoL impact scale by the specialists, representing a moderate-high impact. The MS specialists considered that pain, spasticity, spasms/cramps, bladder dysfunction and depression should be a treatment priority given their frequency and chance of therapeutic success. The neurologists agreed on the usefulness of the new Spasticity-Plus Syndrome concept to manage spasticity and associated symptoms together, and their experience with treatments targeting the cannabinoid system was satisfactory. Conclusions: The applicability of the new concept of Spasticity-Plus in MS clinical practice seems possible and may lead to an integrated management of several MS symptoms, thus reducing disease symptoms’ treatment burden.